Concepts and considerations in the development and implementation of a game plan for american football - Marshall, G. (7th World Congress on Science and Football (WCSF), 2011, 2011)
In preparation for a typical game of American football, coaches have on average one week to prepare the game plan, practice and perfect the plan and then implement it into a game. This presentation will involve what a coach or coaching staff of American football have to take into consideration in formulating an effective offensive game plan. American football is unique in that the game is made up of a series of single plays that are called during breaks in the physical activity or action of the game. Methods In this presentation I will go through how I as head coach and offensive coordinator of the Western Mustangs, formulate the game plan, practice and prepare it and how we implement and adjust it in a in a game situation. Results & Discussion The presentation will go through a typical week of preparation leading up to the game and the implementation of the plan in a game situation. I will go over opponent scouting and factors that affect the formulation of the game plan. Practice and rehearsal of the game plan, which will include the structure of our practices throughout the week, leading up to the game. Our meetings and video sessions and how we use them to implement and prepare for the game. Game day implementation of the offensive game plan and the adjustments that are made to account for the changes in defensive structure and systems, changes in personnel and other variables that may affect our play calling throughout the game. Conclusion What plays are called either offensively or defensively will depend on that game plan and what was practiced throughout the week. The play calls will also be adjusted to take into account the many changing or evolving factors in the game.